Eye Development in Sepia officinalis Embryo: What the Uncommon Gene Expression Profiles Tell Us about Eye Evolution - Imarazene, Boudjema; Andouche, Aude; Bassaglia, Yann; Lopez, Pascal-Jean; Bonnaud-Ponticelli, Laure (Frontiers in Physiology, 2017)
In metazoans, there is a remarkable diversity of photosensitive structures; their shapes, physiology, optical properties and development are different. To approach the evolution of photosensitive structures and visual function, cephalopods are particularly interesting organisms due to their most highly centralized nervous system and their camerular eyes which constitute a convergence with those of vertebrates. The eye morphogenesis in numerous metazoans is controlled mainly by a conserved Retinal Determination Gene Network (RDGN) including pax, six, eya, and dac playing also key developmental roles in non-retinal structures and tissues of vertebrates and Drosophila. Therefore, we have identified and explored the role of Sof-dac, Sof-six1/2, Sof-eya in eye morphogenesis and nervous structures controlling the visual function in Sepia officinalis. We compare that with the already shown expressions in eye development of Sof-otx and Sof-pax genes. Rhodopsin is the pigment responsible in metazoan of light sensitivity: to correlate visual function and eye development, we studied Sof-rhodopsin expression during retina differentiation. By in situ hybridization, we show that 1) all of the RDGN genes are expressed in the eye area during the early developmental stages but they are not expressed in the retina, unlike Sof-otx, which could have a role in retina differentiation; 2) Sof-rhodopsin is expressed in the retina just before the vision is functional, from stage 23, to hatching. Our results evidence a role of Sof-six1/2, Sof-eya, and Sof-dac in eye development. However, the gene network involved in the retinal photoreceptor differentiation remains to be determined. Moreover, for the first time, Sof-rhodopsin expression is shown in the embryonic retina of cuttlefish suggesting the evolutionary conservation of the role of rhodopsin in visual phototransduction within metazoans. These findings are correlated with the physiological and behavioral observations suggesting that S. officinalis is able to react to light stimulus from stage 25 of organogenesis as soon as the first retinal pigments appear.